Blistering rash in a patient with psoriasis - Malieni, Daniela; Guzzi Maqueda, Mariana; Hidalgo Parra, Isabel; Galimberti, Gastón; Kowalczuk, Alicia; Galimberti, Ricardo (Revista del Hospital Italiano de Buenos Aires, 2006)
.